2002
DOI: 10.1038/sj.hdy.6800090
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reproductive compensation on recessive disorders within consanguineous human populations

Abstract: We investigate the effects of consanguinity and population substructure on genetic health using the UK Asian population as an example. We review and expand upon previous treatments dealing with the deleterious effects of consanguinity on recessive disorders and consider how other factors, such as population substructure, may be of equal importance. For illustration, we quantify the relative risks of recessive lethal disorders by presenting some simple calculations that demonstrate the effect 'reproductive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Reproductive compensation, which may occur if the culturally defined 'optimal' family size is less than the reproductive potential of the population, is one of the processes leading to reduced selection and purging. 6 Its occurrence should therefore depend on both environmental conditions and on the strength of selection. This includes variations in physiological condition and in gene expression occurring along an individual's reproductive period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive compensation, which may occur if the culturally defined 'optimal' family size is less than the reproductive potential of the population, is one of the processes leading to reduced selection and purging. 6 Its occurrence should therefore depend on both environmental conditions and on the strength of selection. This includes variations in physiological condition and in gene expression occurring along an individual's reproductive period.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, in modern societies, it appears that such an effect can hardly be assessed through its impact on productivity, owing to reproductive compensation. 5,6 Reproductive compensation refers to the replacement of offspring lost to genetic disorders. It has been suggested that the net productivity of those parents who have lost their offspring can be equal to, or even greater than, the population average.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of death ascribed to recessive gene expression, besides increasing the numbers of subsequent births, reproductive compensation effectively reduces the rate at which recessive disease alleles are eliminated from the gene pool [48][49][50] . But even allowing for continuing marital endogamy and reproductive compensation, the marked reduction in mean family sizes that has occurred in Iran since the 1980s ( fig.…”
Section: Consanguinity Postnatal Mortality and The Prevalence Of Genmentioning
confidence: 99%
“…A detailed review of the outcomes of consanguineous offspring and its relevance to clinical genetics is given by Bittles (2001). Substructure within populations can also lead to a localised increase in the frequency of a recessive allele, and hence disorder (Heinisch et al 1995;Bittles, 2001), but there are important differences with the case of consanguinity (Overall et al 2002). In a subdivided population, genetic drift and founder events can elevate the local frequency of deleterious alleles, especially in societies that have strongly endogamous kinship groups.…”
Section: Introductionmentioning
confidence: 99%